Formative Assessment for mathematics teaching and learning Teacher Professional Development Research by Videoanalysis Methodologies - Ferretti, Federica (Ricerca e formazione, 2018)
This book aims at describing pathways and achievements of the LLP Comenius Project "FAMT&L - Formative Assessment in mathematics for teaching and learning". The main purpose of this research project was to encourage the use of formative assessment in the teaching-learning process carried out by mathematics teachers in lower secondary school. Through the voices of the several actors involved in this project, the book wants to contribute to the international debate on issues regarding teachers' professionalism in the European school systems: specifically, on the development of the professional skills of teachers in the field of assessment practices and on the use of formative assessment in the classroom.